2014
DOI: 10.1111/j.2047-2927.2014.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cannabinoid receptor‐1 activation in mitochondrial depolarizing effect of lipopolysaccharide in human spermatozoa

Abstract: Gram-negative bacteria frequently involved in urogenital tract infections release the endotoxin lipopolysaccharide (LPS); its receptor, toll-like receptor-4 (TLR4), has been recently identified in human spermatozoa, and its direct activation has been suggested in mediating adverse effects of LPS on human spermatozoa. However, the underlying signal transduction remains to be clarified. In other cell types, LPS induces the generation of endocannabinoids, which are involved in mediating endotoxin effects. In huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Studies have indicated that the sperm MMP is positively correlated with ATP content and sperm motility (Barbonetti et al, 2014). The results of this experiment indicated that 50 μmol/L CoQ 10 significantly improved sperm ATP content, MMP, and motility, which is consistent with the above results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies have indicated that the sperm MMP is positively correlated with ATP content and sperm motility (Barbonetti et al, 2014). The results of this experiment indicated that 50 μmol/L CoQ 10 significantly improved sperm ATP content, MMP, and motility, which is consistent with the above results.…”
Section: Discussionsupporting
confidence: 90%
“…This may be related to the scavenging of free radicals by CoQ 10 resulting in inhibition of LPO, which is quite evident from the lower MDA content and ROS content in this group. Studies have indicated that the sperm MMP is positively correlated with ATP content and sperm motility (Barbonetti et al, 2014). The results of this experiment indicated that 50 μmol/L CoQ 10 significantly improved sperm ATP content, MMP, and motility, which is consistent with the above results.…”
Section: Discussionmentioning
confidence: 99%
“…In humans the data are scarce, and largely limited to expression at the RNA level in whole testis tissue extracts, including the testis-dominant expression of CB2A variant 24,25 . At the protein level previous human studies only investigated ejaculated spermatozoa; CNR1 alone was detected in one study 17 , while both CNR1 and CNR2 were found by other groups 19,20,34 .…”
Section: Discussionmentioning
confidence: 86%
“…3). Positive controls were prepared by incubating samples for 1 h at RT with H 2 O 2 (2 mM) and FeCl2Á4H 2 O (1 mM) in a final volume of 200 lL of PBS, as previously described (Barbonetti et al, 2014), before fixation procedure.…”
Section: Assessment Of Sperm 8-ohdgmentioning
confidence: 99%